Effect of Intermittent Fasting Strategies on Cardiometabolic Risk Factors: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials. (7th June 2021) - Semnani-Azad, Zhila; Khan, Tauseef; Kabisch, Stefan; Kahleova, Hana; Kendall, Cyril; Lau, David; Wharton, Sean; Leiter, Lawrence; Lean, Michael; Harris, Leanne; Rahelic, Dario; Salas-Salvado, Jordi; et al.
Abstract: Objectives: Intermittent fasting (IF) is a popular trending diet, yet there is limited evidence-based support considering its clinical impact on cardiometabolic outcomes. In an effort to inform the European Association for the Study of Diabetes (EASD) clinical practice guidelines for nutrition therapy, we conducted a network meta-analysis of randomized controlled trials (RCTs) comparing IF strategies and continuous energy restriction (CER) on cardiometabolic outcomes using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach. Methods: MEDLINE, EMBASE, and Cochrane databases were searched through Nov 2020. We included RCTs assessing the effect of IF strategies (alternate-day fasting (ADF), whole-day periodic fasting (WDF), time-restricted feeding (TRF)), CER, and ad libitum diet. Outcomes included body weight, fasting glucose and LDL-cholesterol. Two independent researchers extracted data and assessed risk of bias. A network meta-analysis was performed and data were expressed as mean differences (MD) with 95% confidence intervals (CI). The certainty of the evidence was assessed using GRADE. Results: We identified 19 RCTs ( n = 590) including adults of varying health backgrounds. ADF and CER both showed a benefit for body weight reduction compared to ad libitum diet (18 trials, n = 520; MD −3.95 kg [95% CI −6.09, −1.81] and MD −2.85 kg [95% CI −4.99, −0.71], respectively). For fasting glucose (17 trials, n = 590), TRF showed a benefit compared to ad libitum diet (MD −0.39 mmol/L [95% CI −0.59, −0.20]), to CER (MD −0.25 mmol/L [95% CI, −0.45 to −0.06]) and to WDF (MD −0.20 mmol/L [95% CI, −0.45, −0.05]). Furthermore, ADF showed a benefit in reducing LDL-cholesterol (17 trials, n = 590) compared to ad libitum diet (MD −0.21 mmol/L [95% CI −0.40, −0.1]), and to CER (MD −0.15 mmol/L [95% CI −0.31, −0.01]). The certainty of the evidence ranged from high to moderate due to variable downgrades for imprecision. Conclusions: Current evidence provides a good indication that IF strategies have similar benefits to CER for weight loss but may have additional benefits for fasting glucose and LDL-cholesterol. Long-term high quality RCTs are needed to clarify the effect of different IF strategies on cardiometabolic outcomes. Funding Sources: Diabetes and Nutrition Study Group of the EASD, Canadian Institutes of Health Research (CIHR), Diabetes Canada.